Problematika dan Prospek Hubungan Antarumat Beragama di Indonesia Masa Orde Baru - Agus Permana (UIN Sunan Gunung Djati Bandung, 2022)
The objective of this article is to reconstruct the political policies of the New Order government regarding inter-religious relations in Indonesia, particularly in chiming with the relationship between religious communities and the government during 1966-1998. The method applied in this research is the historical method with research steps, namely, source collection (heuristic), source analysis (criticism), interpretation and historiography). The results of the study reveal that in general the New Order government in the period 1966-1998 took a two-way policy towards the religious community, namely on the one hand developing religious life in rituals and avoiding the religious community from political discourse. From this policy, the term “Tri Kerukunan” (Tri Harmony) emerges. which indicates a tripartite relationship between religious adherents, internal religious communities, people, and the government which is more dominated by a discourse on the relationship between Muslims and the government or the state. At the level of ideological-political policies related to inter-religious relations, the government develops exclusive and centralistic policies. Meanwhile, at the socio-religious level, since the beginning, the government has developed quite pluralist policies. This pluralist tendency can be seen from the participation of extra-state elements in policy formulation. Thus the format of government policies regarding inter-religious relations is not merely religious but is framed with macro policies, especially in the fields of politics and ideology.